2017
DOI: 10.1002/jia2.25017
|View full text |Cite
|
Sign up to set email alerts
|

Online interventions to address HIV and other sexually transmitted and blood‐borne infections among young gay, bisexual and other men who have sex with men: a systematic review

Abstract: IntroductionGlobally, young gay, bisexual and other men who have sex with men (gbMSM) continue to experience disproportionately high rates of HIV and other sexually transmitted and blood‐borne infections (STBBIs). As such, there are strong public health imperatives to evaluate innovative prevention, treatment and care interventions, including online interventions. This study reviewed and assessed the status of published research (e.g. effectiveness; acceptability; differential effects across subgroups) involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 74 publications
(344 reference statements)
0
22
0
1
Order By: Relevance
“…To date, however, there has not been a comprehensive review summarizing the scope and use of digital health interventions that currently exist for this population. Knight et al [ 54 ] recently reviewed web-based interventions for HIV or sexually transmitted infection (STI) risk reduction in young men who have sex with men (MSM); however, this review did not capture digital health interventions that are delivered through other digital modalities (eg, mobile apps), those that address other health issues, or those that target women, gender-diverse individuals, or individuals with intersex variations. There have also been several recent reviews focused on the mental health of LGBTIQ+ young people [ 55 , 56 ] and adults [ 57 ], which have referenced a combined total of 4 digital interventions for this population.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, there has not been a comprehensive review summarizing the scope and use of digital health interventions that currently exist for this population. Knight et al [ 54 ] recently reviewed web-based interventions for HIV or sexually transmitted infection (STI) risk reduction in young men who have sex with men (MSM); however, this review did not capture digital health interventions that are delivered through other digital modalities (eg, mobile apps), those that address other health issues, or those that target women, gender-diverse individuals, or individuals with intersex variations. There have also been several recent reviews focused on the mental health of LGBTIQ+ young people [ 55 , 56 ] and adults [ 57 ], which have referenced a combined total of 4 digital interventions for this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, these important intermediate outcomes are not always measured in the evaluations of combination prevention programmes, which limit our understanding of how and why they work 6 10. One reason may be that it can be more challenging to measure empowerment, for example, than to measure traditional HIV prevention outcome such as HIV incidence, protected intercourse and recent HIV testing 11 13–19. Besides, there are no widely accepted or standardised methods to measure broad concepts such as improved agency to demand human rights and increased experiences of inclusion despite being core components of a programme’s overall strategy 18 19.…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 systematic review of 17 internet-based interventions that targeted HIV knowledge and risk behaviors among young MSM, demonstrated that all except one reported statistically significant changes in at least one primary outcome, indicating that such interventions showed promise to affect change among this population. [36].…”
Section: Plos Onementioning
confidence: 99%